584. Prospective Observational Cohort Study of Serological Responses to COVID-19 Vaccines in Pediatric Kidney Transplant Recipients at a Single Institution. (15th December 2022) - Goggin, Kathryn P; Sun, Elizabeth; Yun, Emily J; Kamel, Margret; Perez, Maria; Hsiao, Hui-Mien; Anderson, Evan J; Shane, Andi L; Liverman, Rochelle; George, Roshan; Rostad, Christina A
Abstract: Background: Pediatric kidney transplant recipients (PKTR) are at risk of poor outcomes from COVID-19. Data on serologic responses to COVID-19 vaccines in PKTR remain sparse. We characterized the magnitude, breadth, and longevity of SARS-CoV-2 spike protein binding antibody responses in PKTR. Methods: This single institution, prospective observational study enrolled PKTR presenting to a transplant clinic for routine care who had received or were eligible to receive a COVID-19 vaccine. Demographic data, history of prior COVID-19, and vaccination details were collected. Plasma samples obtained from standard-of-care residual specimens were analyzed for SARS-CoV-2 spike variant IgG using the MesoScale Discovery V-PLEX platform, which quantitatively measures antibodies to SARS-CoV-2 full-length spike wild-type (Wuhan-hu-1), Alpha (B.1.1.7), Beta (B.1.351), Delta (B.1.617.2), Gamma (P.1), and Omicron (B.1.1.529; BA.1) variants. Vaccine time points with > 5 samples available were analyzed. Geometric mean titers (GMTs) were calculated and log-transformed titers were compared using one-way ANOVA with Tukey's post-hoc comparisons test. Results: 61 PKTR enrolled (Table1); 47 (77%) received at least 1 dose of COVID-19 vaccine in transplant clinic. 47 (77%) PKTR had at least one sample available for analysis, but serial specimens were lacking for many. By 6 months post-dose 2 of COVID-19 mRNA vaccination, spike (Wuhan-hu-1) IgG titers had waned to pre-vaccination levels (GMT 24 vs 47 binding antibody units (BAU)/mL, P=0.988). Administration of a 3 rd dose of mRNA vaccine significantly boosted IgG antibodies (GMT 492 BAU/mL, P=0.007), and titers were maintained at 3 months (GMT 656 BAU/mL, P=0.001) but gradually waned by 6 months (GMT 223 BAU/mL, P=0.070). Administration of a 4 th dose elicited a non-significant increase in titers (GMT 905 BAU/mL, P=0.870). Binding IgG antibodies to SARS-CoV-2 variant spike proteins post-vaccination were not significantly different from Wuhan spike. Conclusion: In this cohort of PKTR, a 3 rd dose of COVID-19 mRNA vaccine significantly boosted broadly cross-reactive binding IgG antibodies to SARS-CoV-2 spike variants, including Omicron. Decreasing titers at 6 months post-dose 3 raise concern for waning protective immunity and support 4 th dose vaccination. Disclosures: Evan J. Anderson, MD, GSK: Advisor/Consultant|GSK: Grant/Research Support|Janssen: Advisor/Consultant|Janssen: Grant/Research Support|Kentucky Bioprocessing, Inc: Data Safety Monitoring Board|MedImmune: Grant/Research Support|Medscape: Advisor/Consultant|Merck: Grant/Research Support|Micron: Grant/Research Support|NIH: Funding from NIH to conduct clinical trials of Moderna and Janssen COVID-19 vaccines|PaxVax: Grant/Research Support|Pfizer: Advisor/Consultant|Pfizer: Grant/Research Support|Regeneron: Grant/Research Support|Sanofi Pasteur: Advisor/Consultant|Sanofi Pasteur: Grant/Research Support|Sanofi Pasteur: Data Adjudication and Data Safety Monitoring Boards|WCG and ACI Clinical: Data Adjudication Board Andi L. Shane, MD, MPH, MSc, International Scientific Association for Probiotics and Prebiotics (ISAPP): Honoraria Christina A. Rostad, MD, BioFire Inc, GSK, MedImmune, Micron, Merck, Novavax, PaxVax, Pfizer, Regeneron, Sanofi-Pasteur.: Grant/Research Support|Meissa Vaccines, Inc.: Co-inventor of RSV vaccine technology licensed to Meissa Vaccines, Inc.|NIH (Funding from NIH to conduct clinical trials of Moderna and Janssen COVID-19 vaccines): Grant/Research Support.